Wear and friction performance evaluation of nickel based nanocomposite coatings under refrigerant lubrication. (August 2020) - Bhutta, Muhammad Usman; Khan, Zulfiqar Ahmad
Abstract: Environmental concerns related to global warming has enforced the introduction of newly artificially formulated refrigerants. HFE-7000 is a replacement solution for the existing harmful refrigerants and thermo-fluids having a broad range of application areas including usage in green energy, low carbon technologies, in aerospace and automotive industries. In this study five different types of coatings namely, Ni–ZrO2, Ni–Al2 O3, Ni–SiC, Ni-Graphene and Nickel-only have been used to study the wear and friction performance of these coatings in systems based on HFE-7000 refrigerant. Extensive experimentation has been performed on these coated contacts using a modified pressurised lubricity tester by changing the refrigerant temperature and the applied normal load in an attempt to enhance the tribological performance of interacting machine parts employing HFE-7000. EDS analysis performed on all the sample pairs within the contact region revealed the presence of fluorine and oxygen based tribo-films. These oxygenated and fluorinated tribo-films help prevent metal-to-metal contact leading to a drop in friction and wear. All coatings presented an improvement in the micro-hardness and in hardness to elastic modulus ratio compared to uncoated steel. The results of friction and wear of coated samples were compared to uncoated steel as well. The results show an improvement in wear and friction at most of the operating conditions by applying Nickel based coatings on a steel substrate in the presence of HFE-7000. Friction and wear performance of Nickel based coatings does drop for some of the coatings at particular testing conditions which leads to conclude that a careful selection of the coatings has to be made depending on the operating refrigerant temperature and load. The results of this study provide a guideline and will be extremely useful in selecting the type of coating based on the application area. Highlights: Friction and wear analysis of HFE-7000 subject to nickel based coatings for sustainable design solutions. Wear performance enhancement at a range of testing conditions by using Nickel based coatings. Improvement in friction coefficient at various operating conditions by using Nickel based coatings. Chemical reaction between the rubbing surfaces and the refrigerant, HFE-7000. Formation of protective anti-wear tribo-films on the rubbing metals.